Selling Women : Prostitution, Markets, and the Household in Early Modern Japan - Stanley, Amy, 1978- (Book collections on Project MUSE., 2012)
This book traces the social history of early modern Japan's sex trade, from its beginnings in seventeenth-century cities to its apotheosis in the nineteenth-century countryside. Drawing on legal codes, diaries, town registers, petitions, and criminal records, it describes how the work of "selling women" transformed communities across the archipelago. By focusing on the social implications of prostitutes' economic behavior, this study offers a new understanding of how and why women who work in the sex trade are marginalized.